The Consortia Century: Aligning for Impact - Garmulewicz, A (Oxford University Press, 2025)
The Consortia Century presents a bold prediction: Consortia will be the defining institutional arrangement of the twenty-first century. Consortia are not new, but they have growing importance in addressing societal challenges that exceed the capacity of any single organization. The Consortia Century documents the many challenges facing consortia. Overcoming these challenges, we present a model for achieving sufficient stakeholder alignment for collective action. Stakeholder alignment allows interdependent individuals, groups, and organizations to accomplish together what they cannot do separately. © Oxford University Press 2025. All rights reserved.